ICT as an enabler for sustainable development: reflections on opportunities and barriers. Issue 1 (9th March 2015) - Bull, Richard
Abstract : Purpose: – Information and communications technology (ICT) offers a peculiar twenty-first century conundrum, as it offers both a cause and solution to rising carbon emissions. The growth in the digital economy is fueling increased energy consumption while affording new opportunities for reducing the environmental impacts of our daily lives. This paper responds and builds on Patrignani and Whitehouse's overview of Slow Tech by providing examples of how ICT can be used to reduce energy. Encouraging examples are provided from the field of energy and buildings and implications for wider society are raised. Design/methodology/approach: – This paper builds on the previous overview "The Clean Side of Slow Tech", based on a comprehensive knowledge of literature of the latest developments in the field of digital economy, energy and sustainability. Findings: – This paper provides clear and encouraging signs of how ICT can be used to contribute to sustainability through controlling systems more efficiently, facilitating behavioural changes and reducing energy consumption. Future challenges and recommendations for future research are presented. Originality/value: – This conceptual paper presents the latest research into the use of ICT in energy reduction and offers cautious, but encouraging signs that while the environmental impact of ICT must not be overlooked, there are benefits to be had from the digital economy.